The system in broken. - Sansom, Ian (TLS. Times Literary Supplement, 2025)
The article focuses on a symposium at the University of Cambridge honouring the legacy of computer security expert Ross Anderson, highlighting his profound influence on the field. Topics include the evolution of security engineering, the dangers of centralized databases and corporate overreach, and the belief in open, transparent, and socially responsible digital systems.